Challenges of Energy Saving in the Wastewater System - Kseniia, Kseniia; Skryl, Vitaliya (International Journal of Engineering and Technology, 2018)
The purpose of this study is to determine a number of energy-saving measures in the wastewater system. The methodological basis of this study is the General scientific dialectical method of cognition, under research which the object is studied as a dynamic system in the process of its development. Formation of the main water disposal system directions development was carried out on the basis of dialectical, historical, mathematical, statistical and systematic methods. Methods of comparison, analysis and synthesis, induction and deduction were used in the study and generalization of scientific and practical developments. Also, the study is based on legal and economic instruments, the development of research institutions and academic economists. The study identified the main components of the structure of the wastewater tariff. The structure of water utilities tariffs in 40 organizations of in different regions of Ukraine is analyzed. It is revealed that the specificity of pricing requires non-traditional approaches to the analysis and processing of primary statistics. That is why iterative approaches to tariff modeling have been applied. This made it possible to form a model of factors affecting the formation of the cost of wastewater disposal. Taking into account the constant tendency of increasing the cost of electricity, which is one of the components of the cost of services, the possibility of introducing energy-saving measures was considered. Thus, it was proposed to replace the old pumping stations with new more economical ones. A comparative analysis of the systems characteristics and calculating the planned savings from the reconstruction of the pumping station were presented. The scientific novelty of the results is in the development and calculation of the economic effect of the introduction of energy-efficient pumping stations, which will contribute to the preservation of tariffs for wastewater services.Â